The Role of Culture Power: Examining the Influence of Popular Culture in Shaping Global Power Dynamics - Gautam, Uddhav (Unity Journal, 2024)
Establishing a causal link between popular culture and global power dynamics is challenging as it does not produce tangible outcomes. There is a lack of academic consensus on whether cultural power equates to soft power despite the growing influence of the media and entertainment industry. Considering popular culture a soft power in cultural diplomacy, this article examines the changing paradigms of content moderation and regional lockout in the global power dynamics through case studies of the Korean wave, American Pop culture, and Japanese Manga and Anime. It uses the Saunders Research Onion method with an interpretive approach to subjectively explore the aspects of cultural influence. Similarly, it analyses the evolution of recurring themes in the case studies. Data collection employs a longitudinal approach to study the impact of technology and changing audience preferences. The primary data sources include expert interviews, supplemented by secondary sources such as relevant literature, reports, and media contents. The findings highlight that cultural diplomacy as a softpower approach effectively contributes to the nation-branding concept that now incorporates new demands, actions, and goals.